Two paths to a science of politics (2004)
Dossier sobre el tema: Introduction, Henry E. Brady. Identities, Interests, and the Future of Political Science, Rogers M. Smith. Puzzles, Proverbs, and Omega Matrices, Jim Granato and Frank Scioli
Keywords: Ciencia política